2022
DOI: 10.1007/jhep02(2022)045
|View full text |Cite
|
Sign up to set email alerts
|

Emergent symmetry in Brownian SYK models and charge dependent scrambling

Abstract: In this work, we introduce a symmetry-based approach to study the scrambling and operator dynamics of Brownian SYK models at large finite N and in the infinite N limit. We compute the out-of-time-ordered correlator (OTOC) in the Majorana model without charge conservation and the complex model with charge conservation, and demonstrate that in both models taking the random average of the couplings gives rise to emergent symmetry structures. The random averaging exactly maps the operator dynamics of the Majorana … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 82 publications
4
12
0
Order By: Relevance
“…• Just as there are multiple states within each charge sector, there are also multiple operators [49]. The variable ξ controls the choice of the operator once the charge is fixed.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…• Just as there are multiple states within each charge sector, there are also multiple operators [49]. The variable ξ controls the choice of the operator once the charge is fixed.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…This is justifiable for two reasons, firstly, it is expected that in the case of scrambling dynamics, the non-symmetric operator-strings will decay exponentially fast, leaving behind only the symmetric strings after a short time. Secondly, it has also been shown that features such as Lyapunov growth and the scrambled steady-state are entirely contained within this symmetric irrep, making it the only relevant sector to study the chaotic behavior of the model [49]. For the Brownian model, starting from a symmetric operator-string completely restricts the dynamics to the symmetric sector, which can be seen from the emergent algebra structure.…”
Section: Map From Operator Strings To Su(4) Basismentioning
confidence: 99%
See 3 more Smart Citations